칩 테스트를 위한 UART-to-APB 인터페이스 회로의 설계 - 서영호; Young-ho Seo; 김동욱; Dong-wook Kim (한국항행학회논문지, 2017)
칩을 개발하는 과정에서 설계된 칩의 검증을 위해 FPGA (field programmable gate array)를 많이 이용한다. FPGA에 다운로드 된 회로를 검증하기 위해서는 FPGA로 데이터를 입력해야 한다. PC와 외부 보드를 통한 칩과의 통신을 위한 많은 방식이 있지만 가장 간단하고 쉬운 방법은 범용 비동기화 송수신기 (UART; universal asynchronous receiver/transmitter)를 이용한 방식이다. 최근 대부분의 회로는 AMBA (advanced microcontroller bus architecture) 버스에 연결되도록 설계되어 있다. 즉, 설계된 회로를 검증하기 위해서는 UART를 거친 후에 AMBA 버스를 통해 데이터를 전달해야 한다. AMBA 버스도 최근에 버전 4.0까지 거치면서 다양한 버전이 존재하는데 간단히 테스트를 하기 위한 용도로는 APB(advanced peripheral bus)가 적합하다. 본 논문에서는 UART-to-APB인터페이스를 위한 회로를 설계하였다. Verilog HDL을 이용하여 설계된 회로는 Altera Cyclone FPGA에서 구현되었고, 최대 380MHz의 속도에서 동작이 가능하였다. Field programmable gate arrays (FPGAs) are widely used for verification in chip development. In order to verify the circuit programmed to the FPGA, data must be input to the FPGA. There are many ways to communicate with a chip through a PC and an external board, but the simplest and easiest way is to use a universal asynchronous receiver/transmitter (UART). Most recently, most circuits are designed to be internally connected to the advanced microcontroller bus architecture (AMBA) bus. In other words, to verify the designed circuit easily and simply, data must be transmitted through the AMBA bus through the UART. Also the AMBA bus has been available in various versions since version 4.0 recently. Advanced peripheral bus (APB) is suitable for simple testing. In this paper, we design a circuit for UART-to-APB interface. Circuits designed using Verilog-HDL were implemented in Altera Cyclone FPGAs and were capable of operating at speeds up to 380 MHz.